Costs for the Region of Arica and Parinacota incurred in compliance with the Treaty of Peace and Friendship of 1904 and other facilities granted by Chile to Bolivia - Thomson, Ian; Bradanovich Pozo, Tomás (Estudios Internacionales, 2015)
In this paper an attempt is made to identify and, where possible, quantify the costs borne by Chile, and especially by the Region of Arica and Parinacota, in favor of Bolivia over and above those obligated by the 1904 Peace and Friendship Treaty between the two countries. The focus is on the two overland channels used by Bolivia to transport goods to and from the port of Arica, i.e. the 11-CH Highway and the Arica to La Paz Railway. It is estimated that the effective subsidy ceded by Chile amounts to at least USD 6.12 per ton transported over the said Highway, based on data covering the period 2001 to 2008. Due to a huge investment plan to be carried out by 2023, this amount can be expected to rise. It excludes the costs borne by Chile resulting from the storage free of charge of goods bound to or from Bolivia in the Arica port area and those due to various preferential charges and tax exemptions. The quantitative assessment also excludes certain external costs which are, however, identified.